PENGARUH BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) DAN NET PROFIT MARGIN (NPM) TERHADAP PERTUMBUHAN LABA PADA BANK NTB SYARIAH - Priska, Priska; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of Operating Expenses on Operating Income (BOPO) and Net Profit Margin (NPM) on Profit Growth at Bank NTB Syariah. The research method used is quantitative with an associative approach. Data were obtained from Bank NTB Syariah's annual financial reports for specific periods. The data analysis technique used was linear multiple regression using SPSS software. The results are expected to demonstrate the extent to which operational efficiency and profitability partially or simultaneously influence bank profit growth. The impact of this research provides input for bank management in managing operating expenses and increasing net profit margins to achieve sustainable profit growth.